Finite strip method computer application for buckling analysis of thin-walled structures with arbitrary cross-sections - Lazzari,Joao Alfredo de (2021)
Abstract The Direct Strength Method (DSM) is a well-known formulation presented in the Brazilian standard ABNT NBR 14762:2010, that estimates the strength capacity of cold-formed steel (CFS) members. However, this formulation requires the elastic critical buckling loads as point of departure, regarding local (L), distortional (D) and global (G) modes, which can be obtained by (i) elastic buckling analysis or (ii) available direct equations. The present study is dedicated to the development of a computer program, FStr Computer Application, with graphical user interface (GUI), in order to make the buckling analysis easier and approachable for both research activities and engineering design of thin-walled structures with arbitrary cross-sections (sections combining closed cells with open branches). The proposed application uses the Finite Strip Method (FSM), mainly focused on a simple and accessible GUI, which was implemented in the MATLAB App Designer. Validation of the FStr was performed with the help of examples of open and closed cross-sections and comparison with the results of acknowledged computer programs, such as CUFSM and GBTul, based respectively on FSM and GBT (Generalized Beam Theory), as well as analytical procedures for the case of the global buckling modes. Both, the critical buckling loads expressed by the computed signature curve and the correspondent critical buckling modes are compared, confirming the adequate performance of the proposed computational tool. As future research, the authors plan updates for the FStr Computer Application, including the computation of the buckling modal participation and the automatic strength predictions, based on the DSM-based design prescriptions.